Associations of Work-Family Conflict, Job Satisfaction, Family Satisfaction and Life Satisfaction: A Study of Married Female Secretaries - Ahmad, Aminah (Universiti Putra Malaysia Press, 1996)
This study examined the consequences of work-family conflict through path analytic associations of work family conflict, job satisfaction, family satisfaction and life satisfaction. Data were obtained from 120 married female secretaries in the state of Selangor, Malaysia. Work-family conflict was shown to significantly lead to lower job satisfaction as well as family satisfaction. In addition, both job satisfaction and family satisfaction were significantly related to life satisfaction. The results of the study imply that work-family conflict is an important concern for individuals and organizations alike because of its negative consequences leading to reduced job satisfaction as well as family satisfaction and hence to reduced life satisfaction.